Paper strip sensor based on γ-fe2O3@prussian blue nanozyme for H2O2 detection - Zoha Babaei Afrapoli; Sharmin Kharrazi; Fardin Amidi; Ramin Rahimnia; Reza Faridi-Majidi (Nanomedicine Journal)
Objective(s): High levels of hydrogen peroxide (H2O2) induce oxidative stress in physiological environments. Elevation of H2O2 levels in semen can be a reason for male infertility, by causing protein and enzyme denaturation, lipid peroxidation, and DNA damage. Oxidative stress can affect sperm features, such as viability, motility, and fertilization potential. Although nanozymes are widely used to detect H2O2 using different techniques, monitoring of H2O2 in physiological fluids remains a challenge that has not been studied extensively. We report on a non-enzymatic paper strip based on γ-Fe2O3@Prussian blue nanoparticles (γ-Fe2O3@PB NPs) and their performance for H2O2 detection in buffer and seminal plasma. Materials and Methods: γ-Fe2O3 NPs were synthesized using chemical coprecipitation method and were then coated with PB. γ-Fe2O3@PB NPs were characterized using ultraviolet-visible spectroscopy (UV-vis), dynamic light scattering (DLS), X-ray diffraction (XRD), and transmission electron microscopy (TEM). The results confirmed formation of relatively monodisperse and approximately 71 nm γ-Fe2O3@PB NPs. The peroxidase-like activities of γ-Fe2O3 NPs and γ-Fe2O3@PB NPs were measured using UV-visible spectroscopy. Results: The results demonstrated that the catalytic activity of  γ-Fe2O3@PB NPs was higher than that of γ-Fe‌2‌O3 NPs. The concentrations of γ-Fe2O3@PB NPs and TMB, immobilized on paper strips, were optimized. The detection limit of the constructed lateral flow assays (LFA) for H2O2 in acetate buffer was 50.0 µM. Citric acid and ascorbic acid, as common components in semen, showed interference with the performance of paper strips. The γ-Fe2O3@PB NPs-based paper strip could detect H2O2 spiked in human seminal plasma in 20 min with a detection limit of 750.0 µM. Conclusion: The colorimetric detection of H2O2 on paper strips was successful and quantification of the results was possible with the help of a cell phone, which makes it a breakthrough in quantitative rapid tests.